Idiopathic sudden sensorineural hearing loss – A 12-month review - Ali Malikka; Joe Jacob Kandoth; John Mathai (Asian Journal of Medical Sciences, 2023)
Background: Idiopathic sudden sensorineural hearing loss (ISSNHL) is a condition which is difficult to define and treat. Sensorineural hearing loss being a situation where rehabilitation therapy with hearing aids is the only treatment option, ISSNHL is an exception which can be treated medically if identified early enough. Aims and Objectives: The aim of the study was (i) to calculate the recovery of hearing and other symptoms in patients diagnosed of ISSNHL treated with medical management as per institutional protocol and (ii) to determine the association between recovery with medical management and factors such as time of presentation and comorbidities in patients with ISSNHL. Materials and Methods: In the Department of ENT, MCH, Kottayam, a protocol for the management of ISSNHL was worked out as per guidelines from standard otology textbooks. All patients with suspected ISSNHL were admitted. Hearing assessment was done using pure tone audiometry during inpatient care and on discharge of the patient. Patients were discharged after completion of the treatment and followed up for a period of at least 6 months. Results: The inference of our study is that cases who presented early in the first 24–48 h of onset of symptoms have maximum chance of recovery irrespective of associated comorbidities. Conclusion: The study highlights the fact that ISSNHL is and should be considered as a medical emergency.